Clinician-friendly lower extremity physical performance measures in athletes: a systematic review of measurement properties and correlation with injury, part 1. The tests for knee function including the hop tests. Issue 10 (10th December 2014) - Hegedus, Eric J; McDonough, Suzanne; Bleakley, Chris; Cook, Chad E; Baxter, G David
Abstract : Objective: To review the measurement properties of physical performance tests (PPTs) of the knee as each pertain to athletes, and to determine the relationship between PPTs and injury in athletes age 12 years to adult. Methods: A search strategy was constructed by combining the terms 'lower extremity' and synonyms for 'performance test', and names of performance tests with variants of the term 'athlete'. In this, part 1, we report on findings in the knee. The Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines were followed and the Co nsensus-based S tandards for the selection of health M easurement In struments (COSMIN) checklist was used to critique the methodological quality of each paper. A second measure was used to analyse the quality of the measurement properties of each test. Results: In the final analysis, we found 29 articles pertinent to the knee detailing 19 PPTs, of which six were compiled in a best evidence synthesis. The six tests were: one leg hop for distance (single and triple hop), 6 m timed hop, crossover hop for distance, triple jump and single leg vertical jump. The one leg hop for distance is the most often studied PPT. There is conflicting evidence regarding the validity of the hop and moderate evidence that the hop test is responsive to changes during rehabilitation. No test has established reliability or measurement error as assessed by the minimal important change or smallest detectable change. No test predicts knee injury in athletes. Conclusions: Despite numerous published articles addressing PPTs at the knee, there is predominantly limited and conflicting evidence regarding the reliability, agreement, construct validity, criterion validity and responsiveness of commonly used PPTs. There is a great opportunity for further study of these tests and the measurement properties of each in athletes.